(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Using modern educational tools, the essay informs readers about the study of biophysics in the medical field. Information about modern pedagogical methods for teaching biophysics is available in medicine. Today, the university professor is no longer the main source of information when teaching biophysics to medical students; instead, he expresses his views on the need to broaden students’ perspectives on education through the use of various information and communication technologies.